PROBLEMS OF THE JOINT USE OF TRANSBOUNDARY WATER RESOURCES IN CENTRAL ASIA - SIDOROVA, Larisa (CENTRAL ASIA AND THE CAUCASUS, 2008)
The joints use of water resources has been urgent problem in Central Asia for many years now. And although during the fifteen years of their independence, the region’s countries managed to avoid large-scale water conflicts, the debates still going on about the changes in the conditions regarding use of the Syr Darya and Amu Darya transboundary rivers are creating an atmosphere of looming uncertainty and arousing justified worries about the region’s future. At different stages in its evolution, mankind has constantly come up, in one way or another, against the problem of water shortage. One hundred and forty-five states of the world share so-called trans-boundary water basins with neighboring countries, and twenty-one states are located entirely on the territory of international basins.1 Having to share water resources, particularly if they are limited, often leads to tension in interstate relations. The problem of the joint use of transboundary rivers as such gained momentum in the 20th cen-tury, when reservoirs, diversion canals, and other water-development works began being built on a global scale. As of today, most of these water-development structures have been built on 300 major rivers running through the territory of two or more countries. This has aroused the concern of the countries downstream, since these facilities have entailed a decrease in the amount of water reaching these countries or the sea, and have also had an impact on the state of the ecosystems along the entire riverbed. Some of the largest environmental disasters were related to states’ refusal to cooperate in cross-border water issues or because such cooperation came too late. A graphic case in point is Lake Chad. Its area today is only 10 percent of what it was 40 years ago.2 For a long time, countries have been trying to settle water disputes by diplomatic means. The legal conditions relating to cross-border water resources are regulated by international conventions and treaties that apply to the signatory states or to the countries that have joined them. There are two international conventions that regulate interstate relations with respect to the use of cross-border water resources—the Convention on Environmental Impact Assessment in a Transboundary Context (1991) and the Convention on the Protection and Use of Transboundary Watercourses and International Lakes (1992). These documents are of immense international and political importance, but they are only recommendatory in nature and primarily touch on environmental problems. The mentioned Conventions say very little about the actual problems of river water management and do not envisage a mechanism for settling international disputes.